Analysis of Customer's Trust and Motivation on Insurance Service Purchase Decisions In PT. Panin Dai-Ichi Life Medan - Tommy Tommy; Triana Melinda Sinaga (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of trust and motivation on purchase decision of PT. Panin Dai-Ichi Life. This type of research is explanatory research. The population in this study were all customers of PT. Panin Dai-Ichi Life Palang Merah during the 2020 period, totaling 244 customers. The technique of determining the sample is by using the Slovin formula with a standard error of 5% so that 152 samples are obtained. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that trust and motivation partially or simultaneously have a positive and significant effect on purchase decision of PT. Panin Dai-Ichi Life. Based on the results of this study, the implications for management are to further improve trust and motivation.